PERANCANGAN SISTEM INFORMASI TRYOUT UJIAN NASIONAL BERBASIS KOMPUTER ONLINE - Edy Widodo; Heni Khasanah2 (Jurnal SIGMA, 2019)
The progress and success of a school can be seen from the school's graduation data. Graduation rate is an indicator of success achieved by schools through the Computer Based National Examination (UNBK) stage, to prepare for this students must be accustomed to tryouts so they can be more trained and ready to face UNBK, but there are still many schools that have not been able to carry out national exam tryouts computer based online. The purpose of this research is to design an online computer-based national exam tryout information system, while the system development methodology used is a waterfall, the results of this study are successfully created an online computer-based national exam tryout information system. The conclusion of this study is this system can facilitate students in preparing themselves to take the Computer-Based National Examination. Keywords : Tryout, UNBK, Ujian Online